A total systems improvement study on the pre-development stage of Sta. Clara Power Corporation - Mirano, Alan Dominique; Pangilinan, Therese Denelle; Peña, Emmanuel Johann III; Reyes, Justine Aethelberht (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
This study aims to provide an analysis on the pre-development stage (PDS) of SCPC based on the way the company conducts the processes as well as the timeline of the conduction of those processes to determine the main problem areas of the company, and provide timely and appropriate solutions. For the first part of the study, the proponents determined the vision, mission, and goals of the company to ensure that any analysis and recommendation that they will provide would align with the company's objectives. They focused on analyzing the situation perceived by the company as a problem. They conducted interviews and gathered available data necessary to conduct a root cause analysis. For them to be able to determine the main problem point, the proponents documented the current processes of the PDS based on the interviews and data gathered. They located areas in the processes where problems mostly occur and the symptoms they manifested. Currently, they have already lost 2 power plants to Ayala due to inefficiencies in the system, wherein some processes were done haphazardly, amounting to a loss in potential revenue of PHP 112.5 million yearly. Thus, they looked for benchmark processes and timelines from other institutions that would help set a standard to compare to, since SCPC currently does not have any standard because they are a relatively young company. They found out that SCPC's planned timeline is lagging behind by 181 days compared to their planned timeline. They scrutinized the root cause behind the lag and they found out that one of the causes is the lack of manpower. Currently, they have only 2-3 people carrying out the processes in the PDS of 16 mini hydro power plant projects. Given the number of steps in the PDS, the workload for a single person is too much to handle within the given timeframe. Additionally, they do not have any way to align all the departments on the status of the projects and thus, have no way of knowing whether they are on track, may it be with time or money. Lastly, their employees do not have the proper training to avoid haphazard conduct of the processes. They even allow casual recruitment of employee peers with only a travel allowance to provide, which cannot guarantee a quality output. All problems point to the evident lack, if not absence, of proper project management. If not remedied, each day of delay would cause the company to lose as much as PHP 13 million of potential earnings for the 16 service contracts. From the findings, the proponents proposed recommendations to improve the company's lack of proper project management. The proponents provided a step-by-step procedure to aid them in transitioning from their current system to adapting a proper project management practice. The proponents proposed the creation of a Work Breakdown Structure (WBS) based on the steps provided by the Gesellschaft fur Internationale Zusammenarbeit (GIZ) timeline and the adoption of the consolidated duration resulting from the combined timelines of Private Company X, Min DA, and DOE. They also proposed determining costs for each step resulting in the WBS, and as a result proposed the allocation of manpower based on proximity of the projects' areas. Furthermore, the proponents proposed using Failure Mode and Effects Analysis (FMEA} in assessing the risks the company may encounter. The proponents analyzed some of the company's risks and as a result, came up with a solution to ensuring that those risks were properly dealt with which is through the utilization of a central monitoring system which would not only track the planned versus actual completion of the PDS steps, but also the costs accompanying those steps and which can also be used to update the entire company of the active projects' status.
Submitted in partial fulfillment of the course requirements in IE 155 : Total systems study.
Keywords: Hydroelectric power plants -- Philippines; System analysis